THE IMPLEMENTATION OF “MURDER MYSTERY GAME’ TO TEACH SPEAKING OF NARRATIVE TEXT TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 21 SURABAYA (RETAIN, 2014)
THE IMPLEMENTATION OF “MURDER MYSTERY GAME’ TO TEACH SPEAKING OF NARRATIVE TEXT TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 21 SURABAYA Genggam Prayudha Wiradini English Education Departement, Faculty of Language and Art, State University of Surabaya genggampw@hotmail.com Ririn Pusparini, S.Pd., M.Pd. English Education Departement, Faculty of Language and Art, State University od Surabaya rrn.puspa@gmail.com Abstrak Speaking mengambil peranan penting dalam pembelajaran Bahasa Inggris dan harus dikuasai oleh siswa dengan baik. Sebelumnya, beberapa siswa berpendapat bahwa speaking adalah aktifitas yang berat karena mereka merasa susah untuk menata kata-kata secara langsung. Oleh karena itu, dibutuhkan guru yang mempunyai kreativitas and cara yang sesuai untuk menyampaikan materi agar kemampuan speaking siswa menjadi baik Pada penelitian ini, “Murder Mystery Game” sebagai teknik yang disarankan kepada guru untuk membantu siswa agar tertarik aktifitas speaking di kelas. Sebagaimana Erzos (2002) berpendapat bahwa game dapat digunakan untuk memberikan banyak praktek pada komunikasi. Penelitian ini mengacu pendeskribsian implementasi “Murder Mysteru Game” pada pengajaran speaking teks narrative untuk kelas delapan dan juga untuk mengetahui kemampuan siswa berbicara setelah pengimplementasian game ini. Penelitian ini menggunakan deskriptif kualitatif. Subyek pada penelitian adalah kelas delapan di SMP Negeri 21 Suarabya di kelas VIII-A. Data pada penelitian adalah hasil darpada observasi, catatan lapangan, transkrip siswa dan questionnaire. Datanya dianalisa secara deskriptif untuk menjawab pertanyaan-pertanyaan penelitian. Hasil penelitian memperlihatkan bahwa implementasi game ini berada segaris dengan tujuh langkah-langkah pada pembelajaran speaking. Hasil transkrip siswa memperlihatkan bahwa siswa dapat berbicara lebih baik karena pengimplementasian “Murder Mystery Game”. Selebihnya, aktifitas guru berada segaris dengan prinsip-prinsip pengajaran speaking. Berdasarkan hasil-hasil tersebut, dapat dilihat dari nilai siswa, pengimplementasian “Murder Mystery Game” dapat membantu siswa berbicara secara narrative. Dan sebaliknya, kemampuan siswa berbicara juga terlihat baik. Kata Kunci: speaking, narrative text, game, murder mystery game Abstract Speaking takes an important role in learning English and it should be mastered by the students well. Yet, some of the students consider that speaking is difficult activity because they feel difficult to arrange the words naturally. Thus, it needs the teachers who have creativity and appropriate ways to deliver the material in order to improve the students’ ability in speaking. In this study, “Murder Mystery Game” as a technique is considered to the teachers to help them to make an interesting activity speaking class. As Erzos (2002) states that games can be used to give practice many types of communication. This research aims to describe the implementation of “Murder Mystery Game” in speaking of narrative text for the eighth graders. It also aims to know the students’ ability in speaking after the implementation of this game. This study is descriptive qualitative research. The subject of this research is the eighth graders in SMP Negeri 21 Surabaya at class VIII-A. The data in this research are the result of observation, field note, students’ transcription, and questionnaire. The data are analyzed descriptively to answer the research questions. The result of the observation showed that the implementation of this game was in line with seven stages in teaching speaking. The result of the students; transcription showed that students can speak more active by the implementation of “Murder Mystery Game”. Moreover, the teacher’s activity was in line with principles of teaching speaking. Based on those result, the implementation of “Murder Mystery Game” helped the students to speak in Narrative. It could be shown in the students score. Meanwhile the students’ speaking ability showed better. Keywords: speaking, narrative text, game, murder mystery game. INTRODUCTION There are four basic language skills that should be practiced by people, there are; listening, speaking, reading and writing. These four basic skills are categorized into two, receptive and productive. Among these four skills, speaking is one of the productive skills that aim to communicate with others in spoken words, and it is very important in daily communication. It is supported by Herbert (1977:56) that “speaking is a basic of human activity”. In communication, people put ideas into words talking about perception, feeling and intension. Mastering the art of speaking is the single most important aspect of learning a second or foreign language and success measured in terms of the ability to carry out the conversation in language (Nunan, 1977:56). Speaking skill also takes an important role in learning English. In learning English as a foreign language, especially for junior high school, students get difficult to have conversation on a topic that they know little about (Baker and Westurp, 2003:5). Most of the students consider that speaking is difficult activity because they have to arrange words into good sentences and they feel ashamed if somebody figures out the grammatical mistakes. In addition, Mafruchah (2009) states in her thesis that “in the speaking activity, students of junior high school still get difficulties in expressing ideas. They are afraid seemed reluctant in front of their classmates because of their mistakes and if the teacher asks the students to practice, they prefer to keep silent”. It is happens, because the students do not have their self confidence and lack of motivation from the teacher who sometimes chooses uninteresting materials in the learning process. To gain the students’ interest in the speaking activity, it needs the teacher who was able to choose an interesting topic which is familiar to students’ speaking materials and set up a real life condition in order not to make the students get bored. As Sauvignon (1980:34) in her book says that the importance to the learner’s progress in variety of activities in which the students can use language in the real situation which created by the teachers and can avoid students’ boredom. Furthermore, the teacher should create an active speaking class atmosphere, stimulate students’ motivation, likeness, curiosity, develop students’ acquisitions in learning English, as well as should be creative enough to implement a technique in order to make her or his students enjoy and comfortable with the activity in learning process. There are many kinds of techniques that can be used in the speaking class, there are: role play, discussion group, debate, games and so on. All of them represent strategies for providing the emotional involvement necessary for authentic interaction in the classroom (Sauvignon, 1976: 41). One of the techniques that seems to encourage the students’ speaking ability is game. Halliwell says that, “Games provide an opportunity for the real language use” (1992:6). Wright as cited by Kenongo (1983:1) states that games also help and encourage many learners to sustain their interest and work. From these statements, it can be said that games mostly enjoyable and fun for students. In addition, students are encouraged to express themselves freely in the language from the beginning through experiences and games which provide them with framework for spontaneous, communicative creation (Rivers, 1978:6). It means that by using and playing the games, students will be free to express their ideas without feel afraid to speak something and make mistakes. “Murder Mystery Game” is not a new game and usually played by the teenagers of Western people at the end of dinner party activity. As Hadfield (1987) classifies languages games into more categories and some of them are problem-solving games and role play games. “Murder Mystery Game” is an adaption games from problem-solving games and role play games because the students are expected to work in a group that includes five until six students and they have their own secrets and rules, take a role, expected to be the player and try to solve the problem to find who the real murderer is as stated in the paper they got from their teacher. By using this game, the students are demanded to interact with the members of the group and speak freely in longer utterances on the topic given The advantages of this game are the students can interact and share opinion among the member of the group and also the teacher can observe the students’ speaking ability from each group. Moreover, based on the standard competence 2006, narratives deal with problematic events which lead to a crisis or turning point of some kinds, which in turn finds a resolution. “Murder Mystery Game” seems appropriate for students in learning speaking narrative text because the contents are orientation, complication and resolution. Depdiknas (2006: 35) states that the function of narrative text is to entertain. Hopefully, by the implementation of “Murder Mystery Game”, there will be any encouragement of students’ speaking ability in the classroom. Based on the background of the study above, the research questions are formulated as follows: 1.2.1 How is the implementation of “Murder Mystery Game” in teaching speaking of narrative text to the eight grade students of SMP Negeri 21 Surabaya? 1.2.2 How is the students’ speaking ability toward the implementation of “Murder Mystery Game” in teaching speaking of narrative text to the eight grade students of SMP Negeri 21 Surabaya? 1.2.3 What are the students’ responses in the implementation of “Murder Mystery Game” in teaching speaking of narrative text to the eighth grade students of SMP Negeri 21 Surabaya? Speaking Speaking is a mean of expressing or delivering opinions. People communicate through an oral expression to get much more information. According to Bailey (2003: 48) speaking is the productive skill that people use to communicate orally. In learning a foreign language, speaking skill is as important as other three skills. Agustien (2004: 6) also says that naturally speaking, people learn spoken language first before they learn written version. It means that, speaking plays an important role in order to communicate with others, especially speaking English because nowadays English is considered as an International language. David as cited by Kenongo (2010: 7) “there are generally five components recognized in the analysis of the speaking process: (1) Pronunciation, including the segmental features, vowels, consonants, stress, and intonation patterns; (2) Grammar; (3) Vocabulary; (4) Fluency, the ease and speed of the flow of the speed; (5) Comprehension. However, the students should not to master all of the language components but they can improve their language components by practice speaking. In addition, River (1970: 35) states that “students of a new language will not learn to speak fluently by hearing speech in class, since speaking skill involves active participants on the part of students”. So the teacher should activate the speaking class and give the opportunities to the students to practice their speaking as much as possible. Game One useful technique to encourage language acquisition is using language games. When using games in the classroom, it is beneficial for teachers to have a complete understanding of the definitions of games, which usually are defined as a form of play concerning rules, competition, and an element of fun (Deesri, 2002). Games also help the teacher to create context in which language is useful and meaningful. Of course, in this case, the teacher should be careful to make the games enjoyed by young learners and at the same time some language items are learned. Brown (1985:317) states that games involve: 1. Rules which must be followed 2. Competition between individuals or teams 3. Determination of a winner if teams of players are part of the games plans, cooperative learning as well as competition can result. The game also has many advantages. They make the students more easily to understand the teacher’s instruction, strengthen the students’ understanding of the context of learning. Kinds of Games According to Hadfiled (1987), “language games can be divided into two further categories: Linguistic games and communicative games. Linguistic games focus on accuracy, such as applying the correct antonym. On the other hand, communicative games focus on successful exchange of information and ideas, such as two people identifying the differences between their two pictures which are similar to one another but not exactly alike. Hadfield (1987) also classifies language games into many more categories as follow: • Sorting, ordering or arranging games: For example, students have a set of cards with different products of them, and they sort the cards into products found at a grocery store and products found at a department store. • Information gap games: In such games, one student has access to the information which is not held by the other student, and this student must acquire the information to complete the task successfully. Information gap games can involve a one-way information gap or a two way information gap. • Guessing games: In these games, someone knows something and the others must find out what it is. • Matching games: As a name applies, participants need to find a match for a word, picture or card. • Labeling games: These are form of matching game, in that participants match labels and pictures • Puzzle-solving games: The participants in the game share or pool information in order to solve a problem or a mystery. • Role play games: The terms role play, drama and simulation are sometimes used interchangeably but can be differentiated. Role play can involve students playing roles that they do not play in real life, such as dentists, while simulations can involve students performing roles that they already play in real life or might be likely to play, such as a customer at a restaurant. Dramas are normally scripted performances, whereas in role plays and simulations, students come up with their own words, although preparation is often useful. Narrative Text According to 2004 English curriculum (Depdiknas, 2004b: 3) the structure of narrative comprises Orientation (sets the scene and introduce the characters), Complication (a crisis/ problem arises), and Resolution (the crisis is resolved for better or worse). Narrative is a familiar type of communication to entertain the listener and the reader with a real or fiction experience. Some types of narrative are fairy stories, mystery, science, fiction, horror/ scary, fable, adventure, romance, and etc. Narrative also has some characteristics based on its linguistic features (Depdiknas, 2004a: 6), those are: Specific participant and individual participant In the narrative text that tells chronological story consist of orientation, complication and resolution. In this word, narrative text shows the specific participant or individual participant. It means event that happens with repetition of the participant in the sentence. Many action verbs (material process) A sentence is consisting of subject, verb and object. In this case, narrative text often uses many action verbs, such as the word walk, run, etc. Verbal process and mental processes sometimes used in the narrative text. The example of verbal process is the word say, tell, etc. The mental process includes the word believe, know, etc. Using past tense In narrative text uses past tense because the story was happened. So the event of the story is not related with activity now. The time signals usually used in narrative text are: once upon a time, yesterday, ago, etc. Using linking words related to time Linking words are used in the narrative text that they do with time such as then, when, one day, etc. So the text seems chronological story because it introduces orientation then complication and finally the participants solve it that is called resolution. Descriptive language Descriptive language means a text that tells to the objective. In this case, the author grows the listeners’ imagination. So he or she can descript the event of the story, such as the word good, bad, beautiful, etc. Using pronouns The pronouns (I, he, she, and they) are often used in the narrative text. In this case, it is easy for the reader to understand the text because of the pronouns is mentioned. Using illustration to support the text. To support the text is needed the illustration. It can help the students to understand the text easily. Moreover it is interesting when the teacher can stimulate the students to feel and imagine the story. Anderson and Anderson (1998: 3) as cited by Widyastiningrum states that narrative text also has some text organizations or generic structures and language features that should be fulfilled in constructing the text, that is: Generic structure of narrative text: First, an orientation in which the narrator tells the audience about who is in the story, when the story is taking place and where the action is happening. Second, a complication that sets off a chain of events that influences what will happen in the story. Third, a sequence of events where the characters react the complication. Fourth, a resolution in which the characters solve the problem created in the complication. Fifth, a coda that provides a comment or moral based on what has been learned from the story (an optional step). Language features of narrative text: First, there are nouns that take the role to identify the specific characters and places in the story. Second, adjectives that provides accurate descriptions of the characters and settings. Third, verbs that show the actions that occur in the story. Fourth, time words that connects events, telling when they occurred. Murder Mystery Game As the writer stated in the previous chapter before that Hadfield (1987) classifies languages games into more categories and some of them are problem-solving games and role play games. “Murder Mystery Game” is an adaption games from “problem-solving games” and “role play games” because the students are expected to work in a group that includes five until six students and they have their own secrets and rules, take a role, expected to be the player and try to solve the problem to find who the real murderer is as stated in the paper they got from their teacher. However, as Schneider and Kortuem (2005) state that “Murder Mystery Game” is the combination between multiplayers with Live-Action Role-Playing (LARP) games. Multiplayer games are based on social interactions as the key feature contributing to the players’ enjoyment. In the other hand, LARP games are the variants of boards’ games that need a real people to play the role. When these games are played with the real people, it will increase the interaction among the members of the players and they remained rare until recently. Implementing “Murder Mystery Game” in Teaching Speaking Narrative Pre-Activity: Step one: Explain to the class that we are going to play a murder mystery game. Everyone will be a character in the game and one of them is the murderer. Give them the background information Step two: Define a class into a group and each group consists of 5 until 7 students. The main character cards all contain clues to working out the mystery. For bigger groups use the supplementary cards (they contain no real clues) or for groups of fourteen or more, split the students into two groups and play the game as a competition to see who can work out the mystery first. Give each student a character card. They need to read and memorize the information. The aim is to act out the game, become the character and not to just read the information from the card. At this point answer any questions students might have about their character. Whilst Activity: Step three: Hand out the worksheets, explain to the class they need to collect information about everyone who was at the party and fill any relevant information on the sheet. At this point go over key vocabulary: alibi, motive, and clue. Step four: This stage is a mingling activity with students asking questions and collecting information. Monitor the language used at this point and correct where necessary. Post Activity: Step five: When the students have spoken to everyone who was at the party, have them go back into their original groups. Take back the character cards. Using the information they have collected, the students try to work out who killed the victim and why they did it. This part of the lesson usually leads to some lively discussion, most students will quickly guess who the killer is but the information needs to be carefully looked at to work out the why. Previous Study: Many colleagues had conducted studies on the same field. The studies are about using games in the teaching of speaking. That is: Jay Schneider and Gerd Kortuem (2010) whose entitled “how to host a problem-solving game supporting face-to-face interactions in live-action roleplaying”. In their study, they found that live-action roleplaying game can be benefitted when two personal devices are in communication they know their owners are in each others social space and can communicate face-to face. They expected that the applications described above to give a tremendous advantage to those game players who use them. Based on the previous study above, the researcher conducted a research entitled “The Implementation of Murder Mystery Game to Teach Spaking of Narrative Text to the Eighth Grade Students of SMP Negeri 21 Surabaya”. The researcher wants to know whether this research can be used in this school. This research is different with the research which have been mentioned above. This research focusses on teaching speaking narrative by “Murder Mystery Game” while the first research focusses in the live communication roleplaying. RESEARCH METHODOLOGY In doing this study, the researcher used descriptive qualitative research, since it more focuses on the process rather than outcomes of the phenomena. The subjects of the study were the English teacher and the eighth grade students of SMP Negeri 21 Surabaya the setting of the study was SMP 21 Suarabaya which is located on Jln. Jambangan IV Surabaya. The researcher collected the data through some instruments. The instruments were observation checklist and field note to gaint the data for the first research question, students’ speaking task result to gain data for the second research question, with Haris’s ESL Composition Profile and closed-structured questionnaire analyzed third research question.. RESULT AND DISCUSSION The Implementation of “Murder Mystery Game” in Teaching Speaking of Narrative Text This observation was done on 3rd November, 13th ovember, and 15th November 2013. It was held to gain the information about the implementation of “murder mystery game” to teach speaking of narrative text to the eighth grade students. In the first meeting, the teacher organized the students to make groups and introduce the topic which was about narrative text. In this observation, speaking narrative text was not a new activity for the students. But, “murder mystery game” was something new for them. Thus, the teacher introduced the use of this technique to make speaking narrative easier and more enjoy full. In the second meeting, the students produced narrative speech in pair groups. In this meeting, the teacher used worksheet to support “murder mystery game”. The teacher asked the students to complete the worksheet by find the real murderer and then discussed it together with their groups. In this activity, the teacher asked the students to perform spontaneously, but still in groups, but pair groups. In the third meeting, the teacher gave the same topic but in different way. The teacher asked the students to rewrite their understanding about the story in narrative text with their own words. Then, the teacher asked the students to retell or perform the story in front of the class without read their story. The students produced narrative speeches toward the story individually. The teacher did it to make the students became more confident. From the students’ performance, the teacher said that most of them had better performance than before. The main reason why games are considered effective learning aids is that "they spur motivation and students get very absorbed in the competitive aspects of the games; moreover, they try harder at games than in other courses" (Avedon, 1971). Naturally when playing games, students are trying to win or to beat other teams for themselves or on the behalf of their team. They are so competitive while playing because they want to have a turn to play, to score points and to win. In the class, students will definitely participate in the activities. Therefore, it is possible for a teacher to introduce students to new ideas, grammar, knowledge and so on. As in the “Murder Mystery Game”, students are so competitive that they want to finish first and participation. They can motivate students to want to learn more. Moreover, they can transform a boring class into a challenging one. The Students’ Speaking Ability in Speaking of Narrative Text after using “Murder Mystery Game” In this part, the researcher wants to discuss the result of students’ speaking of narrative text. The students’ spoken narrative are analyzed based on Haris’ ESL Speaking Rubric (1969), they are: pronunciation, grammar, vocabulary, fluency, comprehension. Most of them could be accomplished well by the students. Based on the result of the students’ speaking tasks, it could be said that the students’ pronunciation was getting better even though it got stagnant in the second but then, it got better in the third meeting. Brown (2007) stated that good pronunciation did not just mean saying individual words or individual sounds correctly. In the second meeting, the mean from the result of the students’ pronunciation there were just a few students got score two that the pronunciations were very hard to be understood, must frequently be asked to repeat. Most of them got score three that there were few errors in pronunciation and pronunciation problem necessitated concentrated listening and occasionally lead to misunderstanding. And some of them got score four who were always intelligible and almost no errors in pronunciation. In the third meeting, the result of the students’ pronunciation score was three point six and the criteria were almost no errors in pronunciation. Fifteen students or a half of the whole students got score three that there were few errors in pronunciation and pronunciation problem necessitated concentrated listening and occasionally lead to misunderstanding. Fifteen others or another half of the students got score four. They were always intelligible and almost no errors in pronunciation. And just two students or a few got score five that had few trace of foreign accent. The next was about the students’ grammar. Generally, both first and second language learners were seen to proceed from knowing a few structures to knowing more and more, from using simple structures to using more complex ones, and from making errors to making a few if any at all (Louma, 2004). In the second meeting, the result of the students’ grammar score was three point four. They made frequently errors of grammar and word-order which occasionally obscure the meaning. There were two students or just few of them got score two that their grammar and word-meaning errors made comprehension difficult. Must often rephrase sentences and restrict them to basic pattern. The rest were thirty students or most of them got score three that made frequently errors of grammar and word-order which occasionally obscure the meaning. And they occasionally made grammatical and word-order errors which did not obscure the meaning. In the third meeting, the result of the students’ grammar score was three point nine. The students occasionally made grammatical and word-order errors which did not obscure the meaning. Some of the students got score three that made frequently errors of grammar and word-order which occasionally obscure the meaning. Meanwhile, there were many students got score four that occasionally made grammatical and word-order errors which did not obscure the meaning. And a few of them got score five. They made few noticeable errors of grammar or word order. Overall, it could be said that the students’ grammar was getting better from the second until the third meeting seen from the means of the score for three meetings which were significantly improved. The next explanation was about the students’ vocabulary. In the second meeting, the result of the students’ vocabulary score was three point five. They frequently used the wrong word because the limited vocabulary but most of vocabularies were correctly used. A few students got score two. They used very limited vocabulary that made the comprehension quite difficult. Some of them got score three. They used an adequate variety of words and most of them were correctly used. And most of them got score four. They used rich variety of words but sometimes used inappropriate word. In the third meeting, the result of the students’ vocabulary score was four point five. They used rich variety of words and almost all of the vocabularies were appropriate. There was a student got score three. She used an adequate variety of words and most of them were correctly used. There were eleven students or many of them got score four, they used rich variety of words but sometimes used inappropriate word. There were twenty students or most of them got score five, they used rich varieties of words and almost all of the vocabularies were appropriate. All in all, it could be said that the students’ vocabulary was getting better from the second until the third meeting seen from the means of the score for three meetings which were significantly improved. The next point was about the students’ fluency. One central part of fluency was related to temporal aspects of speech, such as speaking rate, speech-pause relationship, and frequency of dysfluency marker such as, hesitation, repetition, and self-corrections (Louma, 2004) In the second meeting, the result of the students’ fluency score was two point nine. The students’ speed and fluency were rather strongly affected by language problems. some of the students got score two. They were usually hesitant or often force into silence by language limitation. Most of the students got score three. Students’ speed and fluency were rather strongly affected by language problems. And few of them got score four, their speed or speech seemed to be slightly affected by language problems. In the third meeting, the result of the students’ fluency score was three point nine. The speed or the speaking skill of the students seemed to be slightly affected by language problem beside that the speeches were occasionally hesitant, with some unevenness caused rephrasing and grouping for words. There were some students got score three. Students’ speed and fluency were rather strongly affected by language problems. Most of them got score four. Their speed or speech seemed to be slightly affected by language problems. And few students got score five. Their speeches were effortless and smooth. Overall, it could be said that the students’ fluency was getting better even though it got stagnant in second meeting, but then, it got better in the third meeting. It was told by the mean of the students’ fluency score. The last was about the students’ comprehension. In the second meeting, the result of the students’ comprehension score was three point three. There were few students got score two. They had great difficulties following what they said. They can comprehend only “social conversation” spoken slowly and with frequent repetitions. Many students got score three; other students understood most of what they said at slower than normal speed with repetitions. And most of them got score four. They understood nearly everything at normal speed, although occasionally repetition may be necessary. In the third meeting, the result of the students’ comprehension score was four point one. The students’ speaking was nearly-everything understandable at normal speed, although occasionally repetition may be necessary. Few students got score three. They understood most of what they said at slower than normal speed with repetitions. Most of the students got score four. They understood nearly everything at normal speed, although occasionally repetition may be necessary. And many students got score five. They appeared to understand everything without difficulties. All in all, it could be said that the students’ comprehension was getting better from the first until the third meeting seen from the means of the score for three meetings which were significantly improved. The Students’ Responses to the Implementation of “Murder Mystery Game” in the Speaking of Narrative Class Based on the questionnaire that be used by the writer to know what the students’ responses were good. The “Murder Mystery Game” made the students far from worried because they could speak freely so it could encourage their vocabulary. Based on the result of the students’ responses toward the implementation of “murder mystery game” through the questionnaire, it can be stated in general that most of the students like the implementation of “murder mystery game” in English class very much, most of the students were very interested with the implementation of “murder mystery game” in teaching speaking of English class, most of the students like the teaching material presented in the implementation of “murder mystery game” very much, most of the students understand about the teacher’s explanation in implementing “murder mystery game” very much, and most of the students feel very helped by the implementation of “murder mystery game” in teaching speaking narrative text. From those explanations, it proved that “murder mystery game” was easy to apply. The students enjoy and like to study English especially speaking through using the game, the students like the teaching material presented in the game including the lesson and the media. Besides that, the game could help the students to find the idea when they made a narrative text orally in speaking class. Finally, all of those statements can support the validity or the truth of some experts’ opinion in this study written in chapter one and chapter two. For instance, Uberman states that games are highly motivating and can give the shy students more opportunity to express their opinion and feeling (1988:20). Therefore, because of the implementation of this game forced students to work in groups also in pair, it made the students feel enjoyable and did not feel worry of making mistakes in pronunciation and fluency. CONCLUSION AND SUGGESTIONS Conclusion Based on the result of the data analysis which is obtained through the observation and the student’s speaking, the researcher concludes that: The implementation of “Murder Mystery Game” which was done in three meetings on 3rd, 13th and 15th November 2013 gave a good impact in speaking skill. It can be shown in the result of observation checklist that the teacher gave the suitable material for speaking of narrative text. The game also helped the students to speak up. The result of the scoring criteria and the students’ speaking transcription showed that the students’ speaking ability is better in the third meeting. Although there were many students made mistakes in grammar, pronunciation, vocabulary and so on, that is not the main problem. The most important thing is the students’ courage, spirit, motivation, and interest in participate the class activity which play important role for them in getting success of mastering any material of the lesson. The result of students’ responses toward the implementation of “Murder Mystery Game” was good. This game is considered as positive way in providing an authentic academic setting because the students can practice to have conversation with different partners as many as possible. Suggestions Based on the conclusion above, the researcher gives the following suggestions: First, for the teacher, she should choose the material that appropriate with the students’ interest. She also should not worry with different idea; let the students speak up to tell the story without feel afraid of making mistakes. Second, the teacher should rearrange again the the lesson plan of the activity because the time is limited to conduct the speaking activity. Speaking class needs more time because from speaking, the students also practice their listening and reading. Finally, for the other researcher, it is hoped to be able to find the other subject and media in future that can be observed in order to get better research. REFERENCES Badan Standar Nasional Pendidikan. 2004. Standar Kompetensi dan Kompetensi Dasar Bahasa Inggris. Jakarta. Badan Standar Nasional Pendidikan (BSNP) Baker, Joanna and Westurp, Heater. 2003. Essential Speaking Skill. Britain: Continuum. Halliwell, Susan. 1992. Teaching English in the Primary Classroom. London: Longman. Herbert, Mandeve Clark. 1977. Psychology and Language. New York: Harcourt Brace Jovanovich Inc. Hadfield, Jill. 1987. Elementary Communication Games. UK: Thomas Nelson and Sons. Hadfield, Jill. 1990. Intermediate Communication Games. Edinburg: Pearson Education Ltd Kenongo, Dwi Sukmo. 2010. “Story Games” as a Technique to Teach Spoken Narrative Text to the Ninth Grade Students of SLTPN 1 Candi Sidoarjo. Unpublished Paper: State University of Surabaya. Mafruchah, Atik. 2009. The Use of Survival Games to Improve the Speaking Ability of The Eleventh Grade of Language Class Students at MAN 1 Gresik. Unpublished Paper: State University of Surabaya. Nunan, David. 1997. Language Teaching Methodology. New York: The Mc. Grew-Hill Companies. Rivers, M. Wilga. 1978. Teaching Foreign Language Skill. Chicago: University of Chicago Press. Sauvignon, Sandra J. 1980. Communicative Competence. Theory and Classroom Practice. Massachusetts: Addison-Wesley Publishing Company. Wright, Andrew. Batteridge D, Buckby M. 1983. Games for Language Learning. New York: Cambridge University Press.